Pavlovian Processes in Consumer Choice: The Physical Presence of a Good Increases Willingness-to-Pay - Bushong, Benjamin; King, Lindsay M.; Camerer, Colin F.; Rangel, Antonio (The American economic review, 2010)
This paper describes a series of laboratory experiments studying whether the form in which items are displayed at the time of decision affects the dollar value that subjects place on them. Using a Becker-DeGroot auction under three different conditions—(i) text displays, (ii) image displays, and (iii) displays of the actual items—we find that subjects' willingness-to-pay is 40–61 percent larger in the real than in the image and text displays. Furthermore, follow-up experiments suggest the presence of the real item triggers preprogrammed consummatory Pavlovian processes that promote behaviors that lead to contact with appetitive items whenever they are available.